Sistema de vigilância alimentar e nutricional no Estado de São Paulo, Brasil: experiência da implementação e avaliação do estado nutricional de crianças Food and nutrition surveillance system in the State of São Paulo, Brazil: experience of the implementation and assessment of children's nutritional condition - Sonia Isoyama Venâncio; Renata Bertazzi Levy; Silvia Regina Dias Médici Saldiva; Lenise Mondini; Maria Lúcia Rosa Stefanini (Instituto Materno Infantil de Pernambuco, 2007)
OBJETIVOS: descrever a estratégia de implantação do aplicativo "SISVAN-SP" no Estado de São Paulo e analisar as informações geradas pelo Sistema quanto à distribuição e magnitude dos desvios nutricionais em crianças menores de cinco anos de idade. MÉTODOS: as Unidades Básicas de Saúde dos municípios foram responsáveis pela coleta, digitação e processamento de dados, utilizando um sistema de informações denominado "SISVAN-SP", aplicativo desenvolvido no Instituto de Saúde da Secretaria de Estado da Saúde de São Paulo (SES/SP). Os dados disponíveis mensalmente no sistema são: Direção Regional de Saúde, município, unidade básica de saúde, número do prontuário, data de nascimento, data do atendimento, sexo e classificação do estado nutricional das crianças. Foram consideradas desnutridas as crianças com peso/idade < percentil 3 e em risco de sobrepeso com peso/idade > percentil 97 da curva de referência do National Center of Health Statisics. RESULTADOS: a prevalência de desnutrição variou de 3,1% a 4,2% e a de risco de sobrepeso 4,0 a 4,8% nos diferentes municípios; a qualidade das informações e a cobertura do Sistema, ainda que variáveis, mostraram-se consistentes com informações epidemiológicas. CONCLUSÕES: o aplicativo "SISVAN-SP", desenvolvido pela SES/SP e utilizado para o monitoramento nutricional de crianças até cinco anos de idade, atendidas nas Unidades Básicas de Saúde, mostrou-se útil para avaliar e discutir aspectos do Sistema de Vigilância Alimentar e Nutricional (SISVAN), tais como cobertura e qualidade dos dados. Os resultados apontam para a definição de ações que visem a prevenção e controle de peso dessas crianças. OBJECTIVES: to describe the strategy of the "SISVAN-SP" applicative implementation in the state of São Paulo and analyze the information generated by the System concerning the magnitude of nutritional deviations in children under five years old. METHODS: primary health units in the municipalities were in charge for collecting and entering data using an information system named "SISVAN-SP" an applicative developed by the Health Institute of the Health Secretariat of the State of São Paulo (SES/SP). Monthly available data of the system are: Health Regional Management, municipality, primary health unit, and medical file number, date of birth, date of visit, gender and classification of the children's nutritional condition. Children with weight/age < percentile 3 were considered undernourished and children with age/weight > 97 of the reference curve from the National Center of Health Statistics were considered in risk of overweight. RESULTS: malnutrition prevalence varied from 3.1% to 4.2% and overweight risk from 4.0 to 4.8% in the different municipalities; information quality and System coverage, even when variable were consistent with epidemiological information. CONCLUSIONS: the "SISVAN-SP" applicative developed by SES/SP and used to monitor the nutritional condition of children up to five years old seen at the Primary Health Units was considered useful to assess and discuss aspects of the Food and Nutrition Surveillance System (SISVAN), such as data coverage and quality. Results support decision making aimed at children's weight prevention and control.